RSM approach-based analysis of the physical behavior of dune sand reinforced with Washingtonia waste contributing to mortar cleaner production - Abdelhamid Khelifi; Messaouda Boumaaza; Ahmed Belaadi; Mostefa Bourchak; Tarek Djedid; Ibrahim M.H. Alshaikh; Djamel Ghernaout (Case Studies in Construction Materials)
In today's construction projects, considering the environment and economy is essential. Alternatives to cement or natural aggregates lead to natural resource conservation and reduced carbon dioxide emissions. In this context, dune sand (DS) and Washingtonia waste (WW), which are abundant in the Algerian desert, were investigated as potential eco-friendly substitutes for cement in mortar manufacture. The initiative aims to create innovative, ecological, and cleaner building materials and lightweight, eco-friendly cement mortars. To this end, the response surface methodology (RSM) was applied for predicting and optimizing the physical characteristics of mortars composed of DS and WW, varying from 1 % to 3 % and treated for 4–24 h with sodium hydroxide solution (NaOH) at a 1–5 % concentration. The purpose of this study was to evaluate the suitability of the material for civil engineering, focusing on properties such as slump (S), specific gravity (ρ), water absorption (WA), bending displacement (Yb), dynamic elastic modulus (Edyn), and other properties. Furthermore, the mortar's chemical composition and high-temperature behavior were investigated. To maximize mechanical qualities and minimize physical properties, an analysis of variance using the Box-Behnken Design was performed to optimize and forecast the factors and outcomes. The results revealed that WW content, NaOH concentration, and immersion time significantly influenced the physico-mechanical properties of the mortar. The optimal formulation obtained was 1.3 % WW, 5 % NaOH concentration, and 14.8 h of immersion time, leading to values of 1972.77 kg/m³ for ρ, 16.62 cm for S, 2.63 % for WA, 0.26 mm for Yb, and 20.46 GPa for Edyn. The strong correlation between the RSM model and experimental data confirms the model's reliability. These findings demonstrate the potential of this sustainable mortar for eco-construction applications, such as bending elements and repairing damaged structures in buildings, highways, and bridges.